Endogenous Intoxication in Pulmonary Complications in Patients with Severe Brain Injury - N. N. Yepifantseva; T. I. Borshchikova; Yu. A. Churlyaev; D. G. Dantsiger; N. V. Nikiforova; L. G. Kheringson (Общая реаниматология, 2008)
Objective: to evaluate changes in the laboratory markers of endogenous intoxication in acute severe brain injury (SBI) and to define their prognostic significance in the development of pneumonias. Subjects and methods. Sixty-six patients with isolated severe brain injury in the acute phase of the disease were examined and divided into two groups: 1) 35 (53%) patients who were not observed to have pneumonias in the acute period; 2) 31 (47%) who had developed pneumonia on an average of 7.7±2.8 days after injury. Endogenous intoxication was evaluated from the erythrocytic sedimentation rate (ESR), leukocytic indoxication index (LII), the spectrum of serum medium molecular-weight peptides and red blood cells, complements C3, C4, C-reactive protein, soluble fibrin monomer complexes, dienic conjugates, lactic acid, urea, and creatinine. Immunological parameters, such as the total count of lymphocytes and the level of CD3+ lymphocytes (a marker of mature lymphocytes), were studied by indirect monoclonal antibody immunofluorescence. A control group comprised 24 healthy individuals. The data were statistically processed by the Statistica-6 program, by applying Student’s test, and Pearson’s correlation coefficient. Results. Endogenous intoxication was found to be attended by immunodeficiency and to show two waves; just after injury it was caused by diseased and ischemic brain tissue destruction products and its second wave was associated with the development of pneumonias by the end of the first week after injury when an increase in proteolysis products along bacterial toxemia proved to be of significance. The markers, the predictors of pneumonia development in SBI, are increases in ESR up to more than 40 mm/hour on day 3, ESR up to more than 50 mm/hour, and in complement C3 levels up to more than 1.5 g/l on day 5. The early markers of pulmonary complications are increases in serum medium molecular-weight peptide levels up to over 0.3 optical density units at 262 nm, in C-reactive protein up to more than 100 mg/l, and in dienic conjugates up to above 1.2 mmol/l on day 7. The good predictor of the course of pneumonia is an increase in complement C4 levels up to over 0.4 g/l after day 7 and a reduction in LII to less than 3 relative units. Conclusion. The findings show it necessary to include the diagnostic markers: medium molecular-weight peptides, C-reactive protein, and dienic conjugates into the comprehensive examination of patients with severe brain injury. Key words: severe brain injury, endogenous intoxication, C-reactive protein, dienic conjugates, medium molecular-weight peptides, pneumonias.